End-tidal Carbon Dioxide for Diagnosing Anaphylaxis in Patients with Severe Postinduction Hypotension. (March 2022) - Erlich, Clémence; Lamer, Antoine; Moussa, Mouhamed D.; Martin, Julien; Rogeau, Stéphanie; Tavernier, Benoit
Abstract : Background: Perioperative hypersensitivity reactions may be difficult to diagnose during general anesthesia. Postinduction hypotension is the most common sign but is not specific. It was recently suggested that low end-tidal carbon dioxide (ETCO2 ) might be a marker of anaphylaxis (Ring and Messmer grades III to IV immediate hypersensitivity reactions) in hypotensive patients under mechanical ventilation. To test this hypothesis, the authors compared ETCO2 in patients with a diagnosis of anaphylaxis and in patients with severe hypotension from any other cause after the induction of anesthesia. Methods: This was a retrospective single-center case-control study in which two groups were formed from an anesthesia data warehouse. The anaphylaxis group was formed on the basis of tryptase/histamine assay data and allergy workup data recorded over the period 2010 to 2018. The control (hypotension) group consisted of all patients having experienced severe hypotension (mean arterial pressure less than 50 mmHg for 5 min or longer) with a cause other than anaphylaxis after anesthesia induction in 2017. Results: The anaphylaxis and hypotension groups comprised 49 patients (grade III: n = 38; grade IV: n = 11) and 555 patients, respectively. The minimum ETCO2 value was significantly lower in the anaphylaxis group (median [interquartile range]: 17 [12 to 23] mmHg) than in the hypotension group (32 [29 to 34] mmHg; P < 0.001). The area under the receiver operating characteristic curve (95% CI) for ETCO2 was 0.95 (0.91 to 0.99). The sensitivity and specificity (95% CI) for the optimal cutoff value were 0.92 (0.82 to 0.98) and 0.94 (0.92 to 0.99), respectively. In multivariable analysis, minimum ETCO2 was associated with anaphylaxis after adjusting for confounders and competing predictors, including arterial pressure, heart rate, and peak airway pressure (odds ratio [95% CI] for ETCO2 : 0.51 [0.38 to 0.68]; P < 0.001). Conclusions: In case of severe hypotension after anesthesia induction, a low ETCO2 contributes to the diagnosis of anaphylaxis, in addition to the classical signs of perioperative immediate hypersensitivity. Abstract : From a retrospective single-center case-control study comparing low end-tidal carbon dioxide (ETCO2 ) postinduction in hypotensive patients due to anaphylaxis compared to other causes, a low ETCO2 contributed to the diagnosis of anaphylaxis. The results therefore suggest that in mechanically ventilated patients with severe postinduction hypotension, ETCO2 should be considered as one of the means of distinguishing between anaphylaxis and other potential causes.